Theater Show O Miolo da Estória: Convergence Between Reality and Theatrical Fiction - Silva Da Conceição, Raylson (2023)
This work analyzes the Brazilian theatre play, O Miolo da Estória (The Core of the Story), produced by actor Lauande Aires, through an autoethnography with reflections on my own sensory experiences during the reception of this play, which took place in 2013. In this article, we rescue our memories, dialoguing with the studies of the theorists Santaella (2012) and Merleau-Ponty (1999) on perception, Larrosa (2014) on experience, and Michel Serres (2001) on the skin as the boundary between the body and the world. The relevance of this study is supported by the observation of the functioning of the sensorial senses at the moment of theatrical reception. As a conclusion, the work improves the understanding that this play is composed of two worlds that mix the local culture and the theater.